Spesies Diversity of Gastropods in The Bale Mangrove Ecotourism Area, Jerowaru, East Lombok - Faradila, Baiq Dian; Al Idrus, Agil; Jamaluddin, Jamaluddin (Jurnal Biologi Tropis, 2025)
This study aimed to examine the species diversity of gastropods in the Bale Mangrove Ecotourism Area, Jerowaru, East Lombok. A descriptive-exploratory method was applied using transect-quadrat sampling at three observation stations. At each station, a 100 meter transect line was established, running perpendicular to the coastline. Along each transect, there quadrat plots measuring 5×5 meters were placed alternately at set intervals. Each quadrat was further divided into four sub-quadrants to facilitate detailed recording of individual distribution and abudance. Data were analyzed using the Shannon-Wiener diversity index (H'), evenness index (E), and dominance index (C). The results identified 17 gastropod species from 11 families with a total of 1,194 individuals. The highest diversity was recorded at Station III (H’ = 1.32), while the lowest was found at Station I (H’ = 0.74). Station I also showed the highest dominance index (C = 0.70), indicating strong dominance by Terebralia sulcata. In conclusion, gastropod diversity in the area was categorized as moderate and influenced by environmental factors such as substrate type and pH levels. These findings provide baseline information on the ecological condition of the mangrove ecosystem and highlight the importance of habitat management to support the sustainability of gastropod communities.